The Performance of Fibrous CDC Electrodes in Aqueous and Non-Aqueous Electrolytes - Siret Malmberg (C, 2021)
The aim of this study was to investigate the electrochemical behaviour of aqueous electrolytes on thin-layer (20 µm) nanoporous carbide-derived carbon (CDC) composite fibrous directly electrospun electrodes without further carbonisation. There have been previously investigated fibrous electrodes, which are produced by applying different post-treatment processes, however this makes the production of fibrous electrodes more expensive, complex and time consuming. Furthermore, in the present study high specific capacitance was achieved with directly electrospun nanoporous CDC-based fibrous electrodes in different neutral aqueous electrolytes. The benefit of fibrous electrodes is the advanced mechanical properties compared to the existing commercial electrode technologies based on pressure-rolled or slurry-cast powder mix electrodes. Such improved mechanical properties are preferred in more demanding applications, such as in the space industry. Electrospinning technology also allows for larger electrode production capacities without increased production costs. In addition to the influence of aqueous electrolyte chemical composition, the salt concentration effects and cycle stability with respect to organic electrolytes are investigated. Cyclic voltammetry (CV) measurements on electrospun electrodes showed the highest capacitance for asymmetrical cells with an aqueous 1 M NaNO3-H2O electrolyte. High CV capacitance was correlated with constant current charge–discharge (CC) data, for which a specific capacitance of 191 F g−1 for the positively charged electrode and 311 F g−1 for the negatively charged electrode was achieved. The investigation of electrolyte salt concentration on fibrous electrodes revealed the typical capacitance dependence on ionic conductivity with a peak capacitance at medium concentration levels. The cycle-life measurements of selected two-electrode test cells with aqueous and non-aqueous electrolytes revealed good stability of the electrospun electrodes.